Oral hygiene status of the orphan children in Ar-Rohman Foster Home Bandung after dental health education - Hapsari, Nurayni Tri; Suwargiani, Anne Agustina; Zubaedah, Cucu (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Oral hygiene status is a condition of a personâs oral cavity. Oral hygiene status can be assessed using Oral Hygiene Index Simplified (OHI-S) by Greene & Vermillion. The education given regarding dental health is one of the health promotion with the purpose to increase the ability of children in terms of maintaining and improving their oral hygiene. The purpose of this study was to determine the oral hygiene status of the orphan children in Ar-Rohman Foster Home Bandung before and after being given dental health education (DHE). Methods: This research was pre-experimental research with one group of pretest-posttest design with total sampling technique. Subjects of this research were orphans aged 13-15 years old. The respondents got the clinical examination of OHI-S at before and after the respondent was given dental health education. The data obtained then tested using the normality test, if the data were normally distributed analysis, then analyzed with a paired t-test, and if the data were not normally distributed, will be analyzed with a Wilcoxon test. Results: The results showed aÂ significant decrease of plaque index after dental health education was given to the orphans. The examination of the calculus index (CI-S) did not show any change before and after dental health education. OHI-S of children, however, showed aÂ significant decrease. Conclusion: There was an increase in the oral hygiene status of the orphan children in Ar-Rohman Foster Home Bandung after being given dental health education.